2022
DOI: 10.1186/s12967-022-03607-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiated glioblastoma cell-derived exosomal circ_0012381 induce M2 polarization of microglia to promote the growth of glioblastoma by CCL2/CCR2 axis

Abstract: Background Radiotherapy is the primary therapeutic option for glioblastoma. Some studies proved that radiotherapy increased the release of exosomes from cells. The mechanism by which these exosomes modify the phenotype of microglia in the tumor microenvironment to further determine the fate of irradiated glioblastoma cells remains to be elucidated. Methods We erected the co-culture system of glioblastoma cells and microglia. After radiation, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Exosomal circRNAs also play an important role in the development of glioma, including proliferation, immunosuppression, angiogenesis, invasion, migration, and therapeutic resistance. Recent studies have shown that exosomeassociated circRNAs such as circ_104948, circ_0001445, circHIPK3, circWDR62, circMMP1, circ_0012381 play roles in the glioma proliferation process through miRNAs (30,(96)(97)(98)(99)(100). CircNEIL3 promotes glioma progression and exosome-mediated macrophage immunosuppressive polarization via stabilizing IGF2BP3 (101).…”
Section: Liquid Biopsy Analyses Of Exosomal Circrnas In Glioma Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomal circRNAs also play an important role in the development of glioma, including proliferation, immunosuppression, angiogenesis, invasion, migration, and therapeutic resistance. Recent studies have shown that exosomeassociated circRNAs such as circ_104948, circ_0001445, circHIPK3, circWDR62, circMMP1, circ_0012381 play roles in the glioma proliferation process through miRNAs (30,(96)(97)(98)(99)(100). CircNEIL3 promotes glioma progression and exosome-mediated macrophage immunosuppressive polarization via stabilizing IGF2BP3 (101).…”
Section: Liquid Biopsy Analyses Of Exosomal Circrnas In Glioma Gliomamentioning
confidence: 99%
“…The role of exosomal circRNAs in the development of glioma. Exosomal circRNAs affect the progression of glioma by regulating its proliferation, invasion, migration, angiogenesis, and therapeutic resistance (30,(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109).…”
Section: Figurementioning
confidence: 99%
“…It was highly expressed in the irradiated GBM‐derived exosomes compared with that secreted by non‐irradiated GBM. Exosomal circ_0012381 increased Arg‐1 expression via sponging miR‐340‐5p, which induced the polarization of M2 microglia (C. Zhang, Zhou, et al, 2022). However, the processes of macrophage polarization are complicated and not just related to a single protein (D. Zhou, Huang, et al, 2014).…”
Section: Cancer‐derived Evs‐ncrnas With Immune‐related Cellsmentioning
confidence: 99%
“…For instance, in colorectal cancer, this polarization occurs via the down-modulation of histone deacetylase 11 mediated by miR-145 within colorectal cancer cell-derived EVs [55] . In addition, miR-138-5p, which has been observed in breast cancer-derived EVs, induces an M2-like phenotype in macrophages and promotes tumour growth by inhibiting the H3K27 histone demethylase KDM6B [56] . On the other hand, in brain malignancies, the uptake by microglia of EV-sorted Circular RNAs (circRNA) circ_0012381, which sponges with miR-340-5p, increases ARG1 expression, resulting in CCL2 secretion, which in turn promotes the growth of glioblastoma cells [57] .…”
Section: Immunomodulatory Functions Of Tumour-derived Evsmentioning
confidence: 99%